2018
DOI: 10.1080/01621424.2018.1438952
|View full text |Cite
|
Sign up to set email alerts
|

Home care in Australia: an integrative review

Abstract: The home care sector comprises one of Australia's fastest growing workforces, yet few papers capture the overall landscape of Australian home care. This integrative review investigates home care with the aim of better understanding care recipients and their needs, funding, and regulation; care worker skills, tasks, demographics, employment conditions, and training needs. Over 2,700 pieces of literature were analyzed to inform this review. Results suggest sector fragmentation and a home care workforce who, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…In Canada, as in Australia, the U.S., and U.K., there is a need to strengthen the home care system to meet the demands of the aging population, address the growing pressures on acute care, and manage the subsequent rising costs of healthcare (Canadian Home Care Association, The College of Family Physicians of Canada, & Canadian Nurses Association, ; Hartmann & Hayes, ; Landers et al, ; Morris, ; Palesy, Jakimowicz, Saunders, & Lewis, ). This scoping review explored Canadian literature published over a 13‐year span and identified 32 factors categorised under 7 domains, which were identified for their potential relevance to the optimisation of HCNs.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, as in Australia, the U.S., and U.K., there is a need to strengthen the home care system to meet the demands of the aging population, address the growing pressures on acute care, and manage the subsequent rising costs of healthcare (Canadian Home Care Association, The College of Family Physicians of Canada, & Canadian Nurses Association, ; Hartmann & Hayes, ; Landers et al, ; Morris, ; Palesy, Jakimowicz, Saunders, & Lewis, ). This scoping review explored Canadian literature published over a 13‐year span and identified 32 factors categorised under 7 domains, which were identified for their potential relevance to the optimisation of HCNs.…”
Section: Discussionmentioning
confidence: 99%
“…However, person‐centred care is possible only when staff demonstrate the required values and practices, and work in a suitable environment with supportive processes that enable person‐centred outcomes (Low et al, ; Manthorpe & Samsi, ). Thus, the extent to which improvements may be achieved depends on the service providers’ ability to ensure the quality and continuity of care in a fragmented industry whose workers are typically employed on a casual or part‐time basis (Berglund et al, ; Palesy, Jakimowicz, Saunders, & Lewis, ). Notwithstanding organisational constraints, the value attributed to continuity of care, rapport and communication by people with dementia and family carers, it is likely to be a case of ‘when’, rather than ‘if’, these practices will need to be addressed (Reid & Chappell, ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike countries, such as the United States and Australia, where nursing centers are active with careful monitoring and transparent communication systems (48,49), in some other countries, there is no special organization in charge of undertaking precise and comprehensive examination and evaluation of home care centers (4-6, 10, 12, 15, 18, 19, 21, 22, 24-26, 28, 29, 34, 38, 50, 51). The reason is that in some countries, such as Iran, there is no complete list of legal and illegal centers providing home care and no specific organization has monitored the activity of these centers and their staff is the presence of certain deficiencies in organizational communications (4).…”
Section: Discussionmentioning
confidence: 99%